Avaliação da qualidade tecnológica de grãos de arroz irrigado (Oryza sativa L.) armazenados a granel - (:unkn) unknown (Universidade Federal do Pampa, 2011)
During storage, the grain quality must be preserved to the maximum, given the occurrence of biochemical, chemical, physical and microbiological. The speed and intensity of these processes depend on the intrinsic quality of the grain, the management of technological operations of pre-storage, storage system used, environmental factors during storage and conservation practices employed. This study aims to evaluate the effect of vertical metal storage silos technological quality of grains of rice produced in the region of the western border of Rio Grande do Sul The survey was conducted in partnership with Joaquim Oliveira S. A. Participações - Josapar / Itaqui-RS and analyzed three vertical metal silos, storage for ninety days. Samples were collected from homogeneous grains of rice in two points of the vertical metal silos, ie, the collection was made at the top and bottom of the grain mass. After collecting the grains underwent the following tests for determining the quality of the grains: impurity content, moisture, industrial performance (whole grain yield, percentage of broken grains and incidence of defects), thousand kernel weight and test germination, according to methodologies described in the rules of analysis of seeds. As a result, the qualitative parameters were influenced by humidity and temperature during storage, causing changes and interfering with the quality of grains. The industrial output of grain was influenced by the quantification of defects, which provided a higher percentage of broken grains. The germination and thousand kernel weight showed uniformity in the evaluation period.
Keywords: Armazenamento; Incidência de defeitos; Umidade; Temperatura; Storage; The incidence of defects; Moisture; Temperature; CNPQ::CIENCIAS AGRARIAS